The Determinants Of European Union (EU) Foreign Direct Investments In The EU Countries From Central And Eastern Europe During 1994–2012 - Tang, Donny (Comparative Economic Research. Central and Eastern Europe, 2017)
This study examines whether the CEECs’ financial market development can explain the EU FDI in the CEECs during 1994–2012. The higher bank credit flows had a positive effect on the FDI in 2005–2012. This can be attributed to the major banking sector reforms undertaken before the CEECs’ EU accession. Second, the stock market size had a positive effect in 1997–2004. This is due to the fact that the EU membership announcement facilitated deeper stock market integration. Third, the higher country income, in interaction with a higher bank credit flow, had only a small positive effect in 2005–2012. The higher income CEECs have pursued much deeper bank liberalization through large-scale privatization of state-owned banks. Finally, the higher country income, in interaction with a larger stock market size, had a negative effect in 2005–2012. A possible reason for this is that the EU countries have started to divert their new FDI to the non-EU countries.